Financiamento da educação: análise orçamentária do ensino superior no Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Araújo, Marcelo Pereira de (2021)
Since the creation of the Federal Institutes, according to the Brazilian Law no. 11.892/2008, and the evolution of the rules inherent to accountability, managers, in the scenario of managerial public administration, faced demands from both the academic community and the control bodies regarding their budgetary performance. Seen in these terms, this qualitative, exploratory, and descriptive study aims to search how much was invested in the undergraduate level at Federal Institute of Education, Science and Technology of Paraíba (IFPB) between 2017 and 2019 so that it could be possible to identify the representativeness and the tendency of the funding for this level of education in this institution. The institutional budget for the same period was the object of study. Besides the author`s observation, which was developed based on official documents, mainly from Nilo Peçanha Platform and the Management and Self-Assessment Reports of the period delimited, content analysis of documentary evidence was applied with cross-sectional data method. Specifically, two approaches were used, the first with the purpose of collecting financial data and the second to collect academic data to reach the research's objective. The methodological procedures are presented as follows: characterization of the study, process flow, instruments, universe of research, data collection, and analysis. Thus, based on the theoretical framework and the results, it is concluded that investment in graduation has been reduced, influenced by the low growth of total IFPB investments in the 2017-2019 triennium, enhanced by the contingencies and limitations imposed by constitutional amendment nº 95. Despite the unfavorable investment scenario at undergraduate level at IFPB, in a more analytical view, the technologist degrees received most of investments, with emphasis on the Building Construction course. Secondly, there were the undergraduate courses, with an emphasis on the Brazilian Portuguese language and literature degree, largely due to the expansion of distance learning courses and the legal requirement of 20% of the vacancies offered at IFPB for these types of courses (undergraduate), contributing, especially, with the investments in graduation for the technological axis Educational and Social Development, in which all are undergraduate courses. The research also points out that investments in morning shift and evening shift courses have been falling and the others have been oscillating between losses and gains. Besides, alternatives are presented as a contribution to the construction of the official IFPB reports, highlighting institutional financing as an instrument of public policy and social control.